KAJIAN KEMAMPUAN MUTAN BAKTERI Pseudomonas sp MENDEGRADASI BENZENA DALAM MIKROKOSMOS AIR TANAH - fahruddin, Fahruddin (Jurnal Rekayasa Lingkungan)
Mutation induction with UV can increase microbe capacity in do metabolite includes in mendegradasi polutan’s material. mutagenesis UV’s result from isolat wildtipe Pseudomonas sp (ICBB33p) gotten two mutants which is ICBB33 4 and ICBB33 18. To the effect this research is done to test isolat’s ability that mutant bacteria is deep degradation benzene by compares with isolat parental or wildtipe. Mutant application is done on ground water microcosm that contains to concentrate benzene 125 ppm results benzene concentration decreases 17,82 ppm (86%) for ICBB33’S mutant 4 and 13,37 ppm (89%) for ICBB33’S mutant cell 18 , meanwhile parental’s cell stills to remain benzene concentration as big as 35,8 ppm (70%) of startup concentration 125 ppm. Decrease concentrates benzene, followed by population amount step-up bacteria cell and CO’s amount step-up 2 one that resultant.Key word: biodegradasi’s capacity step-up, UV- mutation, benzene, mutant.